Excavations at Hunterston North Substation, North Ayrshire. Issue 1 (March 2020) - Gordon, Douglas; Rees, Thomas; Turner, Louise
Abstract : Archaeological investigations were carried out between September and October 2014 in association with the construction of a substation for the Kintyre Peninsula to Hunterston subsea electricity cable on the Firth of Clyde. Excavations revealed a probable Early Neolithic structure, a Late Neolithic pit with atypical Grooved Ware, Bronze Age settlement and an intriguing Irish-style Early Medieval cereal-drying kiln. These discoveries are within the immediate landscape context of the extensive excavations undertaken from 2013–14 at Hunterston for the Western Link Project.